Development of Emotional Competence through Music and Movement: Comparative Analysis of the Professional Educational Programs of Prospective Primary School Teachers in Ukraine and Austria - Chernous, Tetiana; Handzilevska, Halyna; Balashov, Eduard; Ratinska, Olena (Journal of Education Culture and Society, 2024)
Aim. The paper focuses on a comparative analysis of the professional education program for prospective primary school teachers in Ukraine and Austria in the context of developing prospective teachers' emotional competence through music and movement and the readiness of prospective primary school teachers to use music and movement in their professional activities and for self-development.Methods. Theoretical research method – the analysis of literature, empirical data acquisition method – questionnaires. The progression of emotional competence, measured empirically through emotional intelligence levels, has been evaluated using Hall's EQ test and Lyusin's Emotional Intelligence Methodology. Statistical data processing has been carried out in IBM SPSS program.Results. The readiness of the majority of respondents to use music and movement means in their professional activities has been revealed. The connection between the indicators of this readiness of the respondents and the readiness to use these means for their self-development has been proved. The relevance of introducing music and movement disciplines into the process of professional training of prospective primary school teachers has been substantiated by the analysis of professional educational programs in Austria and Ukraine.Conclusions. The research revealed the advantage of the indicator by music and movement disciplines in the Austrian`s curricula for general study professional education programmes for prospective teachers in comparison with the Ukrainian ones. The findings of the training programme demonstrate the efficacy of utilising music and movement in nurturing emotional competence